Integration processes in managing innovations in a region = Procesy integracyjne w zarządzaniu innowacjami w regionie - Pomykalski, Andrzej; Pomykalski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
The paper concerns integration processes aimed at business and region development. Effective cooperation should be based on networks that comprise interrelations between organizations, activities and resources.
Keywords: innovation; management; networks; Poland; innowacje; zarządzanie; sieci; Polska